Public perception of flood risks in Klang Valley, Malaysia: a case study - Ahmad Sapawi, Dg Khairunisa; Chew, Jia Ming; Dayang Nur Shahidah, .; Abdul Rahman, Mohd Nordin; Zulkifli, Iliyana; Austin Hew, Tze Yik; Ismail, Mohamad Saupi; Ahmad Wakid, Sarini; Syazwan, Wan Mohd; Okamura, Hideo; Horie, Yoshifumi; Ong, Meng Chuan; et al. (Asia Pacific Academy of Science, 2023)
Floods are becoming a major global concern as these disasters become more severe and frequent. This is no exception to Malaysia as the trend of flood occurrence is increasing year by year. This study aimed to understand the public perception of the flood risks in Klang Valley, focusing on Kuala Lumpur and Selangor metropolitans. A total of 100 respondents participated in this survey via online questionnaire distribution. There are four variables tested in this survey, where factors on environmental concern and anticipating risk have moderate influence on the perception and awareness of flood risk both environmental concern (ß = 0.378, p < 0.000) and anticipating risk (ß = 0.349, p< 0.000) were the only correlations that were statistically significant. It is found that emotional impact (ß = 0.058, p < 0.511) and effort to contribute (ß = 0.148, p < 0.077) did not significantly predict the awareness of flood risks. Further studies are needed to truly grasp the public’s perception of flood risk in Kuala Lumpur and Selangor.